Analisis Dampak Wabah Covid-19 Terhadap Penerimaan (Omzet Penjualan) Pedagang Kuliner Di Kawasan Wana Wisata Kampoeng Ciherang - Muhamad Riziq; Nendah Siti Permana; Tuti Gantini (OrchidAgri, 2023)
The purpose of this study was to determine the performance of Wana Wisata Kampoeng Ciherang before and during the COVID-19 Pandemic, as well as to determine the impact of tourist visits on the acceptance (Sales Turnover) of culinary traders in the Wana Wisata Kampoeng Ciherang area. This research method uses a survey method. 1) Based on the results of research on the performance of Kampoeng Ciherang Tourism before Covid-19, it was a very interesting local tourist area to visit. In addition to the very cool air, there are various games that tourists like. However, with the outbreak of the Covid19 pandemic, the Kampoeng Ciherang Tourism Area fell into a slump because the number of visiting tourists dropped dramatically during the Covid19 pandemic. Wana Wisata Kampoeng Ciherang is also equipped with various culinary offerings provided by food and beverage vendors selling around Kampoeng Ciherang Tourism. During the Covid-19 pandemic, the performance of culinary traders decreased drastically. 2) Before the Covid-19 pandemic occurred, the acceptance of culinary traders in the first month was Rp. 847,381 second month Rp. 655,952 and the third month Rp. 543,095 Meanwhile, during the Covid-19 pandemic, the acceptance of culinary traders in the first month was Rp. 370,238 second month Rp. 247,143 the third month Rp. 173,810 Based on the results of statistical tests using the dependent t-test (paired t-test), that there is a difference between the acceptance (sales turnover) of traders around the Kampoeng Ciherang Tourism Ecotourism area in the conditions before and when Covid-19 occurred.